Analisis Disiplin Kerja Aparatur Sipil Negara Di Kantor Unit Penerimaan Pendapatan Daerah Samsat Biak - Djunaedi Djunaedi; Amiruddin Amiruddin; Yanto Wilfried (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to find out and analyze the level of work discipline of the State Civil Apparatus (ASN) and the factors that affect it at the UPPD SAMSAT Office of Biak Numfor Regency. ASN work discipline is one of the main indicators in assessing the performance of public services, especially in technical agencies that are in direct contact with the community. The main focus of this study is to answer two problem formulations, namely how the level of ASN work discipline is and what are the factors that affect it. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, direct observation, and documentation studies. The results of the study showed that the level of discipline of ASN was quite good, judging from the indicators of punctuality, utilization of facilities, responsibility for duties, and obedience to office rules. However, there are several weaknesses that still need to be addressed, such as late attendance, the use of a digital work system that is not optimal, and violations of rules that are only acted upon with verbal reprimands. The factors that affect ASN work discipline include: leadership, reward and sanction system, individual ability, fairness in the division of labor, inherent supervision, and leadership firmness. These overall results strengthen the relevance of Alfred R. Lateiner's and Hasibuan's theories in explaining the dynamics of discipline in the local government bureaucratic environment. This study recommends the importance of improving the quality of leadership, continuous technical training, strengthening the reward and punishment system, and implementing more consistent supervision in order to form a professional, fair, and accountable work culture for civil servants.